The Potential Of Solar Energy For Domestic And Commercial Buildings - Chee, Kar Wei
In this thesis, financial viability of grid-connected solar photovoltaic (PV) system for domestic and commercial buildings which was investigated through the payback period and return on investment (ROI) is presented. The payback period and ROI were determined and compared based on Feed in Tariff (FiT) scheme and revised Net Energy Metering (NEM) scheme. In Part I of the results, it was found that consumers under Tariff B with monthly electric bill of RM2500 and RM5000 had the shortest payback period at 8.7 years for both schemes. In Part II of results, monthly electric bills of the buildings under the same locations as Part I were obtained and used for analysis. The payback period of commercial building (average bill of RM5003.43) under Tariff B – Low Voltage Commercial Tariff had the shortest payback period at 8.2 years for both schemes which tally with the results from Part I. The ROI of solar PV system installed for this commercial building were 155.03 % (FiT scheme) and 203.65 % (revised NEM scheme). Thus, solar PV system under FiT scheme and revised NEM scheme would be a financially viable option for commercial buildings with monthly electric bill of RM2500 and RM5000 under Tariff B. Lastly, the strategies and plans proposed to support the growth of solar industry in Malaysia were Renewable Portfolio Standard (RPS), Solar Carve Out, Virtual Net Energy Metering (VNEM) and solar energy referral program.